Modeling of Electric Vehicles Fleet's Charging Using Partial Differential Equations - Kajanová, Martina; Braciník, Peter; Kralovič, Michal (Communications - Scientific Letters of the University of Zilina, 2023)
With an increasing number of electric vehicles, their impact on electrical power systems is starting to be substantial. High deployment of these vehicles can even bring issues such as overloading the power transformers and power lines or loss of stability in the power system. Therefore, a suitable model, able to represent large groups or fleets of electric vehicles, is needed to prepare measures that can prevent these problems. The main contribution of this paper is the definition of a charging model representing a fleet of EVs using partial differential equations. This new approach enables meeting the accuracy of the commonly used battery charging models while significantly decreasing required computation times as shown in simulation results.
Keywords: electric vehicle; charging; modeling; partial differential equations